ОБРАЗОВАНИЕ И МОБИЛЬНОСТЬ ТРУДОВЫХ РЕСУРСОВ В ИННОВАЦИОННОЙ ЭКОНОМИКЕ (Journal of Economic Research & Business Administration, 2015)
The article is dedicated to the problems of human resources' mobility and the role of Bolognese process in a broadening of education opportunities.